Different roles for non-receptor tyrosine kinases in arachidonate release induced by zymosan and Staphylococcus aureus in macrophages - Sundler Roger; Olsson Sandra (BMC, 2006)
Abstract Background Yeast and bacteria elicit arachidonate release in macrophages, leading to the formation of leukotrienes and prostaglandins, important mediators of inflammation. Receptors recognising various microbes have been identified, but the signalling pathways are not entirely understood. Cytosolic phospholipase A2 is a major down-stream target and this enzyme is regulated by both phosphorylation and an increase in intracellular Ca2+. Potential signal components are MAP kinases, phosphatidylinositol 3-kinase and phospholipase Cγ2. The latter can undergo tyrosine phosphorylation, and Src family kinases might carry out this phosphorylation. Btk, a Tec family kinase, could also be important. Our aim was to further elucidate the role of Src family kinases and Btk. Methods Arachidonate release from murine peritoneal macrophages was measured by prior radiolabeling. Furthermore, immunoprecipitation and Western blotting were used to monitor changes in activity/phosphorylation of intermediate signal components. To determine the role of Src family kinases two different inhibitors with broad specificity (PP2 and the Src kinase inhibitor 1, SKI-1) were used as well as the Btk inhibitor LFM-A13. Results Arachidonate release initiated by either Staphylococcus aureus or yeast-derived zymosan beads was shown to depend on members of the Src kinase family as well as Btk. Src kinases were found to act upstream of Btk, phosphatidylinositol 3-kinase, phospholipase Cγ2 and the MAP kinases ERK and p38, thereby affecting all branches of the signalling investigated. In contrast, Btk was not involved in the activation of the MAP-kinases. Since the cytosolic phospholipase A2 in macrophages is regulated by both phosphorylation (via ERK and p38) and an increase in intracellular Ca2+, we propose that members of the Src kinase family are involved in both types of regulation, while the role of Btk may be restricted to the latter type. Conclusion Arachidonate release induced by either Staphylococcus aureus or zymosan was found to depend on Src family kinases as well as Btk. While members of the Src kinase family were shown to act upstream of Btk and the MAP kinases, Btk plays another role independent of MAP kinases, but down-stream of the Src family kinases.